Lactobacillus rhamnosus GG Dosage Affects the Adjuvanticity and Protection Against Rotavirus Diarrhea in Gnotobiotic Pigs. Issue 6 (June 2015) - Wen, Ke; Liu, Fangning; Li, Guohua; Bai, Muqun; Kocher, Jacob; Yang, Xingdong; Wang, Haifeng; Clark-Deener, Sherrie; Yuan, Lijuan
ABSTRACT Objectives: The use of immunostimulatory strains of probiotics as adjuvants has been increasingly recognized as a promising approach in enhancing vaccine immunogenicity; however, dose effects of probiotic adjuvants are not well defined. In the present study, we examined dose effects of a commonly used probiotic strain, Lactobacillus rhamnosus GG (LGG), on immunomodulation with 2 different dosages. Methods: Neonatal gnotobiotic pigs were inoculated with 2 oral doses of attenuated human rotavirus (AttHRV) vaccines and fed with 5 doses (LGG5X; total 2.1 × 106 colony-forming units) or 9 doses (LGG9X; total 3.2 × 106 colony-forming units) of LGG, starting at 3 days of age. Results: Both LGG feeding regimens enhanced the protection rate of AttHRV vaccine against diarrhea on virulent human rotavirus challenge. LGG5X, but not LGG9X, significantly enhanced rotavirus-specific intestinal memory B-cell responses to AttHRV; LGG5X also significantly enhanced virus-specific intestinal immunoglobulin A (IgA) antibody-secreting cell responses. Both regimens significantly enhanced rotavirus-specific serum IgA antibody responses to AttHRV. They also enhanced rotavirus-specific interferon-γ–producing effector/memory T-cell responses to AttHRV vaccine, with LGG9X being more effective than LGG5X, and both regimens downregulated CD4+CD25−FoxP3+ regulatory T (Treg) cell responses in most lymphoid tissues examined prechallenge and postchallenge and maintained the CD4+CD25+FoxP3+ Treg population in the ileum and intraepithelial lymphocyte postchallenge. LGG9X, however, did not significantly reduce total CD4+CD25−FoxP3+ Treg frequencies in the intestine and transforming growth factor-β–producing and interleukin (IL)-10–producing Treg frequencies in the blood. Conclusions: These results indicate that LGG at both dosages functioned as effective probiotic adjuvant for AttHRV vaccine, but different dosages differentially modulated immune responses to favor either the mucosal IgA response (LGG5X) or the T-cell response (LGG9X).